Development Strategies for Micro, Small, and Medium Enterprises (MSMEs) in Kampung Singkep - Rafiansyah; Abidin, Zaenal; Dewi, Hasna; Rahmatina A. K (Zabags International Journal of Economy, 2026)
The growing competition between modern and traditional retail sectors has exerted significant pressure on the sustainability of micro, small, and medium enterprises (MSMEs), particularly those operating in staple goods within rural areas. This study aims to identify and understand the development strategies employed by MSME actors in Kampung Singkep Subdistrict to confront the dominance of minimarkets and the challenges they face in increasing profitability. Employing a qualitative approach with a phenomenological strategy, data were collected through in-depth interviews, field observations, and visual documentation, and were analyzed thematically using triangulation techniques. The findings reveal that MSME actors adopt strategies based on service differentiation, community-based distribution, traditional promotion, and the utilization of social capital as adaptive responses to local market dynamics. Key challenges include limited access to capital, low technological literacy, and insufficient institutional support. The study contributes theoretically by integrating a phenomenological approach with competitive advantage theory, product/market growth strategies, and resource-based perspectives, while offering practical insights for designing contextual and community-based MSME development strategies. The implications highlight the need for participatory policy interventions and managerial capacity building to address the complexities of digital economic transformation and intensifying market competition.